Pemanfaatan Media Sosial Sebagai Sarana Promosi Terhadap UMKM Di RT 24 Kelurahan Pematang Gubernur Kota Bengkulu - Malius, Aset; Shinta Kurnia; Yopi Parza; Vethy Octaviani; Maryaningsih; Sri Narti; Asnawati; Merry Rullyanti (Utami Publisher, 2025)
The development of information and communication technology has brought significant changes in various aspects of life, including in the business world. Social media as a digital technology product has become a very effective tool in supporting promotional activities for Micro, Small and Medium Enterprises (MSMEs). With the number of users continuing to increase, social media offers ample opportunities to introduce products and services to a wider market at relatively low costs. The community in RT 24 Pematang District, Governor of Bengkulu City, mostly consists of small business actors engaged in the trade and service sectors. However, they face various problems, such as limited knowledge about the use of digital marketing and lack of access to training in using social media. This causes the potential of social media to be less than optimal as a promotional tool, resulting in stagnant business development. This activity aims to provide solutions to the problems faced by MSMEs, carried out by the Thematic KKN team at RT 24 through a more comprehensive approach. The focus is on implementing social media-based digital marketing that is tailored to local needs, as well as introducing appropriate technology that can support business sustainability. It is hoped that the results of this activity will not only provide practical benefits for business actors, but also become a reference for developing similar programs in other regions.